Epidemiology, Diagnosis and treatment of people living with HIV-2 in West Africa - (:unkn) unknown (My University, 2016)
Background : The holistic care of the one to two million HIV-2 infected individuals in West Africa remain a concern. The frequent misdiagnosis with rapid HIV tests, in addition to the intrinsic resistance of HIV-2 to non-nucleoside reverse transcriptase inhibitors, and its low susceptibility to some protease inhibitors, make the treatment of people living with HIV-2 very challenging. The lack of data on mortality and retention in care among people living with HIV-2, as well as the emergence of resistance to most ART drugs is a great concern for the West African ART program. Method : We relied on the WADA-HIV-2 cohort, its associated biobank and the ANRS 12294 FIT-2 trial, to describe challenges in diagnosis and treatment, as well as mortality and lost to follow up, among people living with HIV-2 in West Africa. Results : One quarter of HIV-2 or dually reactive individuals, according to the national algorithms for HIV diagnosis, were found infected by HIV-1 only, and the tests GenieIII® and ImmunoCombII® showed good performances for a more accurate algorithm. Considering treatment, HIV-2 patients often initiate boosted PI based regimen, with good immunologic and virologic response. A suboptimal response was obtained with either three NRTI based regimens and unboosted PI based regimen, however worse with the first one. HIV-2 infected individuals experienced early and relatively high mortality (5.2/100 person-years), that was associated with anemia and low CD4 count (<100/mm3) at ART initiation. The results of the ongoing ANRS 12294 FIT-2 trial are expected to identify the best strategy for the optimal use of available ART regimens in West African countries. Conclusion : Many questions remain unanswered regarding HIV-2. Epidemiologic, immunologic and genotypic resistances surveys will help improving the care of people living with HIV-2 the West African region.
Keywords: African Research